The Effects of public debt on monetary policy in the Gambia: moderating role of political leadership - Nyang, B. (Strathmore University, 2025)
Public debt is crucial in shaping a country's macroeconomic environment, influencing monetary policy decisions, economic stability, and growth. Managing these debts is critical for developing economies, particularly in sub-Saharan Africa, especially Gambia, where fiscal imbalances often intersect with monetary policy challenges. This study examines the impact of public debt on monetary policy indicators in The Gambia from 1983 to 2022. The method employed was the ARDL approach for the Short-Run, as the results from the F-bound tests indicated that there is no co-integration existing among variables. The correlation results suggested that an increase in foreign debt growth is associated with an increase in the money supply and exchange rate of The Gambia. The study found a moderate positive correlation between public debt and foreign debt, with a weak relationship with inflation and a negative correlation with interest rates. Foreign debt showed a moderate negative correlation with inflation and a strong correlation with both interest and exchange rates. Relationships between foreign debt and money supply or political leadership were weak. Conversely, strong positive correlations were observed among exchange rates, money supply, and political leadership. Increases in public debt positively affect money supply, interest rates, and inflation. Higher public debt correlates with rising exchange rates. Foreign debt significantly affects monetary policy and also positively affects interest rates, inflation and exchange rates. Public and foreign debts significantly influence key economic indicators, with political leadership moderating their effects on monetary policy. The study recommends that The Gambia should prioritize effective foreign debt management alongside domestic debt to achieve sustainable growth and inflation control. Enhanced collaboration between fiscal and monetary authorities, stable political leadership, and adopting proactive fiscal strategies and flexible monetary policies are also recommended to bolster resilience against external economic pressures and ensure long-term stability. Keywords: Short-Run ARDL, Public Debt, Monetary Policy, Political Leadership, Debt Management, Economic Stability, The Gambia.
Full - text thesis